Development communication as part of culture - C.W. Malan (Communicare)
In this survey of approaches to Development Communication (DC) the position is taken that DC, like development itself, should be regarded and studied as part of culture. A cultural perspective is particularly suited to revisit basic DC, communication and cultural concepts that have been obfuscated. Each of these concepts can only be understood within a particular discourse, a framewotk of meaning-producing and sense making, and here the cultural framing predominates. "Oldn and une~ paradigms of DC are compared and relevant policy approaches are surveyed. The main section deals with local knowledge and cultural contexts, and the various functions within a development situation as they relate to communication. In conclusion the importance of "cultural translationn which is regarded as essential to effective DC, is highlighted.